Cortical Connections of Area V6Av in the Macaque: A Visual-Input Node to the Eye/Hand Coordination System - Passarelli, Lauretta (J Neurosci, 2011)
The goal of the present study was to elucidate the corticocortical afferent connections of area V6Av, the ventral subregion of area V6A, using retrograde neuronal tracers combined with physiological and cytoarchitectonic analyses in the macaque monkey. The results revealed that V6Av receives many of its afferents from extrastriate area V6, and from regions of areas V2, V3, and V4 subserving peripheral vision. Additional extrastriate visual projections originate in dorsal stream areas MT and MST. Area V6Av does not receive projections directly from V1; such connections were only observed when the injection sites crossed into area V6. The strongest parietal lobe afferents originate in fields V6Ad, PGm, MIP (medial intraparaietal), and PG, with frontal lobe afferents originating from the frontal eye field, caudal area 46, and the rostral subdivision of the dorsal premotor area (F7). A comparison of their respective connections supports the view that V6Av is functionally distinct from adjacent areas (V6 and V6Ad). The strong afferents from V6 and other extrastriate areas are consistent with physiological data that suggest that V6Av is primarily a visual area, supporting the notion that V6Av is part of a dorsomedial cortical network performing fast form and motion analyses needed for the visual guidance of action.